2013
DOI: 10.1103/physrevx.3.041032
|View full text |Cite
|
Sign up to set email alerts
|

Collision of Akhmediev Breathers in Nonlinear Fiber Optics

Abstract: We report here a novel fiber-based test bed using tailored spectral shaping of an optical-frequency comb to excite the formation of two Akhmediev breathers that collide during propagation. We have found specific initial conditions by controlling the phase and velocity differences between breathers that lead, with certainty, to their efficient collision and the appearance of a giant-amplitude wave. Temporal and spectral characteristics of the collision dynamics are in agreement with the corresponding analytical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
140
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(151 citation statements)
references
References 35 publications
3
140
1
Order By: Relevance
“…[40,41]. A similar synchronized collision of Akhmediev breathers has recently been studied in optics experiments [30], by controlling the phase and velocity differences between the breathers. Figure 1(c) shows the quasiannihilation of breathers at the origin when θ 1;2 ¼ π=2.…”
Section: Breather Formalismmentioning
confidence: 99%
See 2 more Smart Citations
“…[40,41]. A similar synchronized collision of Akhmediev breathers has recently been studied in optics experiments [30], by controlling the phase and velocity differences between the breathers. Figure 1(c) shows the quasiannihilation of breathers at the origin when θ 1;2 ¼ π=2.…”
Section: Breather Formalismmentioning
confidence: 99%
“…These cases provided, as a first step, a powerful framework for interpretation of a specific range of MI-related dynamics that play a fundamental role in the theory of freak waves [23]. Only recently, some unique features of these solutions have been confirmed experimentally for various nonlinear media [24][25][26][27][28][29][30][31]. It concerns the simplest solutions that are either periodic in space and localized in time or periodic in time and localized in space; they are referred to as Kuznetsov-Ma breathers and Akhmediev breathers, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent experiments in water waves [26], [9] and in fibre optics [31], [21], [22], [16] (see also review articles [5], [10]) have convincingly demonstrated that rogue waves are a generic physical phenomenon deserving a comprehensive investigation [27], [5]. It has also been understood that rogue waves play important role in the characterization of the nonlinear stage of modulational instability [41], [17] and particularly, in the development of integrable turbulence [40], [1], [37], [33].…”
Section: Introductionmentioning
confidence: 99%
“…Extreme events have since been observed in many other systems illustrating the wide range of underlying dynamics that can lead to their appearance [2,3]. In an optical context, the recent observation that solitons with extreme spectral red-shifts can emerge from an incoherent fibre supercontinuum [4] has attracted considerable attention and subsequent studies have highlighted the role of nonlinear noise amplification in the spontaneous emergence of highly localised structures [5,6] and the role of collisions in observing long tail statistics [7][8][9].While most rogue waves studies in optics have focussed on the 1+1D fibre case (one spatial dimension and one temporal dimension), the emergence of extreme events during full 3D propagation of light pulses with nonlinear spatio-temporal dynamics has been much less studied [11][12][13][14]. In the normal group velocity dispersion (GVD) regime, the combined action of spatial and temporal selffocusing leads to the formation of a dynamically stable filament characterised by an intense, localised peak surrounded by a weaker reservoir that continuously refuels the central core region [10].…”
mentioning
confidence: 99%